Terapi Perilaku Kognitif (Cognitive Behavior Therapy) untuk Mengatasi Problematica Internet Use pada Remaja - Hanafiyah Nur Liza Rahmadani; Salisa Rahayu Siti; Endang Rifani (UNIVERSITAS BENGKULU, 2024)
This article delves into the detrimental effects of excessive internet usage as a primary cause of PIU and its negative impact on the life balance of adolescents. Employing Cognitive Behavior Therapy (CBT) as a therapeutic approach, the article elaborates on how CBT effectively addresses PIU by reshaping maladaptive thought patterns and promoting healthier behaviors. Previous studies have indicated the efficacy of CBT in addressing internet addiction in adolescents, emphasizing the significance of implementing CBT within the context of individual counseling services. The findings underscore the urgency of proactive intervention to mitigate the adverse consequences of PIU and restore a balanced lifestyle for adolescents. Keywords: cognitive behavior, problematic internet use, adolescents